INVESTIGATING THE EFFECTIVENESS OF ORAL TESTS IN MATHEMATICS IN HIGHER EDUCATION - Law Ka Ho; Chiang Shun Ling (PUPIL: International Journal of Teaching, Education and Learning, 2025)
This study investigated the effectiveness of oral tests as an assessment method in undergraduate mathematics courses in university. It aimed at comparing oral tests and traditional written tests in terms of students’ perceptions and actual learning outcomes in various dimensions, such as conceptual understanding and problem-solving skills. The study consisted of a quasi-experimental design which was employed to compare the scores of students in the same mathematics courses taught by the same instructor but which differ in the assessment mode, i.e. with and without oral test. In addition questionnaire surveys and focus group interviews were conducted to find out students’ perceptions of oral tests as a means of assessment. The comparative study showed that oral assessments were effective in enhancing students’ conceptual understanding, and this was very much echoed by the results of the questionnaire surveys and focus group interviews. The findings support that educators can consider introducing such assessments in courses where the understanding of concepts is an important learning outcome, which typically is the case for theoretical courses targeting mathematics majors.